2019
DOI: 10.1111/tme.12650
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense mutation found in the CD177 gene of Thai individuals with the HNA‐2 null phenotype

Abstract: Summary Objectives The aim of this study is to explore the molecular basis and to develop a simple sequence‐specific primer polymerase chain reaction (PCR‐SSP) technique for screening genotypes associated with the human neutrophil antigen‐2 (HNA‐2) null phenotype among Thai blood donors. Background Single‐nucleotide polymorphisms (SNPs) c.787A>T of the CD177 gene is well known to be primarily demonstrated as a genetic determinant for HNA‐2 deficiency. Methods The SNPs in the CD177 gene (exons 7 and 9) of 49 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The SNP c.787A > T is a nonsense SNP that terminates the protein translation and causes the HNA‐2 expression defect. Our previous study revealed that c.787T homozygosity is the primary genetic determinant for HNA‐2 deficiency, 16 which was confirmed by independent studies from other groups 17,18,23,24 …”
Section: Discussionmentioning
confidence: 53%
“…The SNP c.787A > T is a nonsense SNP that terminates the protein translation and causes the HNA‐2 expression defect. Our previous study revealed that c.787T homozygosity is the primary genetic determinant for HNA‐2 deficiency, 16 which was confirmed by independent studies from other groups 17,18,23,24 …”
Section: Discussionmentioning
confidence: 53%
“…The polymorphism at position c.1254 has been previously reported as a low-frequency polymorphism in a large Asian study [8] where only one homozygous individual was identified. In this case, CD177 expression was not significantly affected (CD177+ 85%, Fig-…”
Section: Discussionmentioning
confidence: 88%
“…First described in 1971 as NB1 [1], the human neutrophil antigen 2 (HNA-2/CD177) has been implicated in numerous clinical conditions including autoimmune neutropenia (AIN), neonatal alloimmune neutropenia (NAIN), transfusion-related acute lung injury and haematopoietic stem cell graft failure [2][3][4][5][6][7]. Although many polymorphisms have been described in the CD177 gene there is no definitive assignment of null or altered expression [4,[8][9][10][11][12][13][14][15][16], which is reflected in the current nomenclature [17]. CD177 null frequency has been reported >10% in French and Western Japanese populations, 3%-5% European, Brazilian and North American populations [10,18] and less than 0.05% in Thai/Chinese [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HNA-2 is an isoantigen and has differential expression on neutrophils. mRNA splicing defects along with DNA polymorphism CD177 * 787A>T in association with c.1254G>A, c.955delG, c.1291G>A SNPs have been identified in several HNA-2-deficient individuals in different ethnic groups [ 11 , 12 , 13 , 14 ]. HNA-2 expression has been more commonly studied by flow-cytometry using monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%